Analysis and presentation of questionnaire data - Stupnicki, R. (University of Physical Education (AWF), 2008)
1. Selection of a representative sample Defining the population studied Estimating population size Estimating sample size Stratification of the population Random selection of objects and individuals Conducting the survey Pilot studies 2. Types of questions and answers Closed auestions with categorised answers Closed auestions with quantitative answers Ranked answers Free-answer questions 3. Designing a question sheet Questionnaire design Arrangement of questions 4. Preparing summary tables Recording data from individual questionnaires Preparing summary tables 5. Analysis of results Analytical summary tables Statistical analysis of frequencies Analysis ofdisjoint choices Analysis ofmultiple choices Analysis of ranked data Analysis of quantitative data Relationships between variables 6. Presentation of results Forms of presentations Description of research procedures Presentation and discussion of results Conclusions 7. Summary